PENERAPAN PRINSIP PERSONA NON GRATA ( HUBUNGAN DIPLOMATIK ANTARA MALAYSIA DAN KOREA UTARA) - Mangku, Dewa Gede Sudika (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2017)
The news of Kim Jong-nams assassination in Malaysia left the North Korean government angry and accused Malaysia of plotting with other countries to kill King Jong-nam. In the process of investigating the murder case, North Korea showed an uncooperative attitude and supported the Malaysian police force, so the Malaysian Government took steps to expel North Korean Ambassador to Malaysia and the same thing was done by North Korea. Malaysia has persona non grata to diplomatic representatives from North Korea as North Korean government does not have the right to resolve this case. In international law especially diplomatic law the application of the principle of persona non grata conducted by Malaysia and North Korea does not conflict with the norms of international law.